Replenishable prevascularized cell encapsulation devices increase graft survival and function in the subcutaneous space - Gauree S. Chendke; Bhushan N. Kharbikar; Sudipta Ashe; Gaetano Faleo; Julie B. Sneddon; Qizhi Tang; Matthias Hebrok; Tejal A. Desai (Wiley, 2023)
Abstract Beta cell replacement therapy (BCRT) for patients with type 1 diabetes (T1D) improves blood glucose regulation by replenishing the endogenous beta cells destroyed by autoimmune attack. Several limitations, including immune isolation, prevent this therapy from reaching its full potential. Cell encapsulation devices used for BCRT provide a protective physical barrier for insulin‐producing beta cells, thereby protecting transplanted cells from immune attack. However, poor device engraftment posttransplantation leads to nutrient deprivation and hypoxia, causing metabolic strain on transplanted beta cells. Prevascularization of encapsulation devices at the transplantation site can help establish a host vascular network around the implant, increasing solute transport to the encapsulated cells. Here, we present a replenishable prevascularized implantation methodology (RPVIM) that allows for the vascular integration of replenishable encapsulation devices in the subcutaneous space. Empty encapsulation devices were vascularized for 14 days, after which insulin‐producing cells were inserted without disrupting the surrounding vasculature. The RPVIM devices were compared with nonprevascularized devices (Standard Implantation Methodology [SIM]) and previously established prevascularized devices (Standard Prevascularization Implantation Methodology [SPVIM]). Results show that over 75% of RPVIM devices containing stem cell‐derived insulin‐producing beta cell clusters showed a signal after 28 days of implantation in subcutaneous space. Notably, not only was the percent of RPVIM devices showing signal significantly greater than SIM and SPVIM devices, but the intraperitoneal glucose tolerance tests and histological analyses showed that encapsulated stem‐cell derived insulin‐producing beta cell clusters retained their function in the RPVIM devices, which is crucial for the successful management of T1D.